2020
DOI: 10.1038/s41523-020-0157-z
|View full text |Cite
|
Sign up to set email alerts
|

BCL9/STAT3 regulation of transcriptional enhancer networks promote DCIS progression

Abstract: The molecular processes by which some human ductal carcinoma in situ (DCIS) lesions advance to the more aggressive form, while others remain indolent, are largely unknown. Experiments utilizing a patient-derived (PDX) DCIS Mouse INtraDuctal (MIND) animal model combined with ChIP-exo and RNA sequencing revealed that the formation of protein complexes between B Cell Lymphoma-9 (BCL9), phosphoserine 727 STAT3 (PS-727-STAT3) and non-STAT3 transcription factors on chromatin enhancers lead to subsequent transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
(85 reference statements)
0
11
0
Order By: Relevance
“…Studies using MIND models to investigate the DCIS-IDC transition have reported on the underlying mechanisms of DCIS progression by using candidate promoters or suppressors. 140 , 149 , 202 , 219 For instance, Elsarraj et al targeted the B cell lymphoma-9 in a MIND model and found that it acted as a promoter of DCIS. 219 Compared to other DCIS xenografts (such as xenotransplants of DCIS cell lines or patient-derived DCIS into the mammary fat pad), MIND models better mimic human DCIS lesions with recapitulation of the initial ductal environment.…”
Section: Tools For Dcis-idc Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using MIND models to investigate the DCIS-IDC transition have reported on the underlying mechanisms of DCIS progression by using candidate promoters or suppressors. 140 , 149 , 202 , 219 For instance, Elsarraj et al targeted the B cell lymphoma-9 in a MIND model and found that it acted as a promoter of DCIS. 219 Compared to other DCIS xenografts (such as xenotransplants of DCIS cell lines or patient-derived DCIS into the mammary fat pad), MIND models better mimic human DCIS lesions with recapitulation of the initial ductal environment.…”
Section: Tools For Dcis-idc Researchmentioning
confidence: 99%
“… 140 , 149 , 202 , 219 For instance, Elsarraj et al targeted the B cell lymphoma-9 in a MIND model and found that it acted as a promoter of DCIS. 219 Compared to other DCIS xenografts (such as xenotransplants of DCIS cell lines or patient-derived DCIS into the mammary fat pad), MIND models better mimic human DCIS lesions with recapitulation of the initial ductal environment. 152 , 221 223 However, all these models are limited by the failure to explore the immune effect in DCIS progression (due to their immunodeficient hosts); they do not therefore fully mimic the natural evolution of human DCIS.…”
Section: Tools For Dcis-idc Researchmentioning
confidence: 99%
“…Published STAT3 ChIP-seq datasets were downloaded and analyzed utilizing Integrative Genomics Viewer (IGV) (28)(29)(30)(31)(32)(33)(34). A public database for aggregated analysis of STAT3 ChIP-seq data ENCODE Transcription Factor Targets dataset (https://maayanlab.cloud/Harmonizome/ gene_set/STAT3/ENCODE+Transcription+Factor+Targets) was provided to predict STAT3 targets (35).…”
Section: Stat3 Transcription Factor Binding Site Prediction In Select...mentioning
confidence: 99%
“…In breast cancer, BCL9 has been identified as a prognostic biomarker for high-risk human ductal carcinoma in situ (DCIS) [ 21 ]. Subsequently, BCL9 has been found to form a complex with STAT3 and to enhance the expression of the genes encoding for integrin β3 and its associated metalloproteinase MMP16 [ 22 ]. Another study has shown that nuclear BCL9L is associated with high nuclear grade and the expression of ErbB2/HER-2 in both DCIS and invasive ductal carcinoma (IDC) [ 23 ].…”
Section: Introductionmentioning
confidence: 99%